Prolotherapy Perineural Injection in Carpal Tunnel Syndrome with Bifid Median Nerve: A Case Report - Tresna Angga Basunanda; Arfano Januar Sangkai (Journal Orthopaedi and Traumatology Surabaya)
Background: Carpal tunnel syndrome (CTS) is a common neuropathy condition caused by entrapment of  the median nerve. Perineural injection therapy with 5% dextrose or prolotherapy becoming a common method for treating carpal tunnel syndrome. Although it is effective, some anatomical variaton of the median nerve could effect the outcome of the prolotherapy in CTS.